Menopause-dependent correlations of blood mercury levels with bone mineral density and appendicular lean mass index in middle-aged women - Xu, Feng; Wang, Yanfei; Fang, Jinqiong; Zhu, Zhongxin (Frontiers in Public Health, 2025)
BackgroundMercury exposure poses significant health risks, yet its effects on bone mineral density (BMD) and appendicular lean mass index (ALMI) in middle-aged women remain poorly understood. This study aimed to investigate the associations between blood mercury levels (BML) and these key indicators of skeletal health and body composition, with special attention to the potential modifying effect of menopausal status.MethodsWe analyzed data from 1,648 women aged 40–59 years (782 premenopausal, 866 postmenopausal) using the National Health and Nutrition Examination Survey (NHANES) 2011–2018. Multiple linear regression models were employed to assess the relationships between LnBML and both lumbar BMD and ALMI, adjusting for relevant covariates.ResultsThere was complex, non-linear associations between LnBML and skeletal health parameters. Notably, the relationship between LnBML and lumbar BMD differed significantly based on menopausal status (P for interaction <0.001). In premenopausal women, LnBML was negatively associated with BMD (β = −0.018, 95% CI: −0.029, −0.007), while in postmenopausal women, a positive association was observed (β = 0.025, 95% CI: 0.014, 0.036). Conversely, LnBML demonstrated a significant positive association with ALMI (β = 0.054, 95% CI: 0.025, 0.083, p < 0.001) in the fully adjusted model.ConclusionOur findings revealed intricate, menopause-dependent relationships between BML and skeletal health parameters in middle-aged women. These results underscore the complex interplay between environmental exposures and women’s health across the menopausal transition, highlighting the need for further research to elucidate underlying mechanisms and inform targeted interventions.